NGINX unit cookbook - DeJonghe, Derek (O'Reilly Media, 2019)
In addition to its popular web server, NGINX now provides a dynamic application server that supports a RESTful JSON API. The open source NGINX Unit server deploys configuration changes without service disruptions and runs apps built with multiple languages and frameworks. With this handy cookbook, developers, DevOps personnel, network admins, and cloud infrastructure pros will learn how to quickly get started with this new server. Hands-on recipes demonstrate NGINX Unit's new approach and describe how to deploy and configure the server for different applications. You'll learn how the comprehensive RESTful API simplifies configuration, how to run applications written in different languages on the same server, and how to use NGINX Unit as the foundation for your service mesh. Recipes in this ebook will help you: Install NGINX Unit using source code, Red Hat- and Debian-based systems, or third-party repositories Configure the server using application, router, and listener objects Explore NGINX Unit usage and operations, including application restart and upgrades Learn how the server provides security through application isolation, Unix user permissions, and API encryption Integrate NGINX Unit with the WordPress content management system and the Django and Express.js web application frameworks.